Manajemen Strategi dalam Lembaga Pendidikan - Komarudin, Komarudin; Siregar, Diana Riski Sapitri; Zahruddin, Zahruddin; Maftuhah, Maftuhah (Lembaga Yasin AlSys, 2022)
Quality educational institutions correlate to the improvement of quality human resources. The better the quality of an educational institution, ideally it will produce good inputs, processes and outputs. Competition in the world of education that is so fast requires managers of educational institutions to think creatively, innovatively and responsively in maintaining and developing their institutions. One of the efforts that can be done is to implement strategic management in managing educational institutions to improve the quality of education. The purpose of this study is to describe strategic management in educational institutions. This type of research used is descriptive qualitative research with literature review method. The data analysis technique in this study refers to the opinion of Milles & Huberman, namely reducing data, presenting data so that it becomes information, and drawing conclusions. The results of this study indicate that the implementation of strategic management can make the management of educational institutions more sensitive to external threats. At least strategic management can also prevent the emergence of various problems that come from inside and outside educational institutions and can also improve the ability of educational institutions to deal with problems. Strategic management will enable educational institutions to carry out all their operational activities in a more effective and efficient manner. Can make educational institutions easy to adapt to changes that occur. Educational institutions that use the concept of strategic management will be more profitable than educational institutions that do not apply it.